2013
DOI: 10.24297/ijmit.v3i2.1367
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Democratic Style of Leadership

Abstract: The paper studies democratic style of leadership and how the style influences the practices of leadership. Leadership can be categorized based on the level of involving team members and participating in the decision making process. The study is exploratory in nature and attempts to explore and analyze the democratic aspects of leadership style and its influence in the practices of leadership. The study adopts survey and interview techniques and 25 leaders of the state Manipur, India are considered as sample. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 2 publications
1
11
0
4
Order By: Relevance
“…However, the research showed that a leadership style, adopted by an organization, greatly influences workplace performance as well as organizational productivity. In a research on democratic style of leadership by Sharma and Singh (2013), they concluded that in regards to their study sample, a significant factor that makes democratic leadership style effective is that majority of the samples are leaders from the government and public sector organizations, where the final decision is usually made by a higher authority.…”
Section: Empirical Review From Some Researchersmentioning
confidence: 99%
“…However, the research showed that a leadership style, adopted by an organization, greatly influences workplace performance as well as organizational productivity. In a research on democratic style of leadership by Sharma and Singh (2013), they concluded that in regards to their study sample, a significant factor that makes democratic leadership style effective is that majority of the samples are leaders from the government and public sector organizations, where the final decision is usually made by a higher authority.…”
Section: Empirical Review From Some Researchersmentioning
confidence: 99%
“…Demokratik liderlik: Demokratik liderler, çalışan üretkenliğinin ve memnuniyetinin artmasına yardımcı olma, çalışanlara rehberlik etme ve çalışanlara yetki devri astların bilgi paylaşımına izin verme gibi çoğu liderlik tarzından daha yüksek çalışan memnuniyeti sağlanır (Sharma, 2013). Ayrıca olumlu bir örgüt ikliminin yaratılmasına yardımcı olan ve astların kararlara katılımlarının sağlanması ile motive edilmelerinden dolayı olumlu bir liderlik tarzı olarak kabul edilirler (Arıkan, 2001).…”
Section: Kriz Dönemlerinde Liderlikunclassified
“…A democratic leader makes decision through consulting his/her employees and soliciting their input or opinion, thus making employees' input valuable by encouraging positive communication, build positive relationships between employees (Sharma & Singh, 2013). Democratic managers depend upon group de-cision making, active member involvement.…”
Section: ) Antecedents Of Workplace Work-place Incivility A) Management Controlmentioning
confidence: 99%